Migration and Regional Development in Timor Leste - Dentinho, Tomaz (2018)
Increasing urbanization is one of the biggest challenges faced by Asian countries. In this case, the growth of cities is due, fundamentally, to huge population growth and rural exodus. Over the next 25 years, Asia's urban population growth by around 70%, to more 2.6 billion people (Asia Development Bank, 2006). This transformation will involve major changes for Asian societies with new forms of housing, employment, consumption and social interaction for individuals and communities. In fact, in the urban areas is easier raising living standards and reducing poverty. The growth of urbanization in Asia has improved the economic development and economic growth of countries; allowed the creation of millions of jobs and the reduction of absolute poverty. The urbanization has changed the people life's (Asia Development Bank, 2006). Migrations are together with the aging population, the world's biggest challenges in the twenty-first century. In The Edge of Migration (Cassel and Miller, quoted in Le Bras, 2000:68) define the current migrations as characterized by four main issues: i) globalization (diversification of countries of emigration and social spectrum of immigrants), ii) its acceleration, iii) differentiation (temporary workers must go par with permanent settlements) and iv) the 'feminization' of the phenomenon. The population movements, both in the case of internal migration, and in the case of international migration are usually linked to differents socio-economic contexts. Populations migrate for regions where there are more and better job opportunities (regions of attraction of population); they migrate for family reasons (eg marriage), to escape a war, an economic crisis, poverty, political persecution as well as to get a better health, but also to escape the disasters (eg, ecological, natural). In other cases, the migration can be based on social constraint, for example, attempt to bring friends or family members who have migrated (Rego et al., 2010). We can consider that migrations are selective. Migration involves a cost, and not everyone have the financial means to make the displacement; on the other hand, not all individuals have personal and social characteristics that allow them to migrate: who migrates is generally younger, with higher levels of education, less risk-averse and therefore more enterprising. Migration flows and the depopulation and urbanization they encompass are eventually the more pervasive effects of globalization. Largest movements will occur between South and West Asia, from Latin to North America, and within Africa (Abel and Sander, 2014). Bravest migrants suffer in the outside borders of Europe, America, Japan and Australia (Baldwin-Edwards and Arango (eds), 1999) or struggle to be recognized in their cities working in informal and formal jobs in construction, agriculture, domestics, tourism, factory work and street hawking, remotely controlled by the authorities, filling the gaps of labor market inefficiencies and hoping to get amnesties and family reunion (Carella and Pace, 2002), but many times unable to build relationships and coherent communities (Dayaratne and Samarawickrama, 2003); a few others migrate to where their skills better fit (Young, 2013) and from the places that global warming hindered livelihoods (McLeman,2011). Others, in countries with loose controls in Africa and South America, migrants agglomerate in the slumps of major towns which, some argue, are the landscape of poverty reproduction (Gugler, 1997; Davis, 2006) while others hope that the formation of slums is just a phase of the urbanization and development process that can be controlled and, in the end solved, by appropriate planning tools; either by a wiser deployment of housing in urban areas (Antrop, 2004; Ooi and Phua, 2007) or through the spatial redistribution of public investment to ensure that income disparities remain politically tolerable (Scott and Storper, 2003). There are also those that are unable to migrate remaining detached in their poor landlocked places or suffering from border wars for the conquest of natural resources. The relationship between migrations flows, development, growth and urbanization is well known and is already properly studied. Around the world, the majority of the population lives in urban areas. The main urban areas are the places than attract more people, are coming from the rural contry areas or from foreign. In general, cities provide better living conditions, better access to work, education, as well as higher income levels. The cities play a strategic role in the evolution of societies and economic development. Yesterday as today, cities are meeting places, promoted the confluence of ideas, people, knowledge and culture. Cities have been the places where changes in economic and productive systems, institutional organization, income growth, structural change and innovation processes are deeply. The larger the size of the city and the capacity to create employment and income, more workers are attracted. In the urban areas, the diversity of economic activities promotes a higher economic growth, though, for example, the sharing of product and factor markets, reducing transaction costs, differentiating inputs and final products and providing a minimum of stability to the market. […] "the skills and agglomeration impact productivity globally in rich and poor countries alike, but that a spatial equilibrium evolves over time. In the poorest places, social ties to home communities are strong. Historically, they provided safety and sustenance". (Chauvin et al. 2016: 42). In the urban areas of Asian countries, educational levels of the population tended to be rising rapidly, both because of rising levels of school attendance over time and a tendency for migrants to this zone, especially those moving out from the city core, to be much better educated than the longer-term resident population, which present, usually whith low education levels (Jones, 2002) Cities are the ideal places for interaction, for exchange ideas; in the urban areas the agents are "mixed". The "meetings" take place between economic, social, political and institutional actors, in formal or informally terms. This relational system reduces transaction costs and facilitates the establishment of agreements; it is the result of spatial, cultural and psychological proximity, which is due to the density, informality, and openness of the cities. In this sense, the economic growth in the urban areas are related to the capacity of cities to encourage innovation, promote the learning processes and disseminate knowledge through the local production system. The importance of urbanization is also significant be it developed or developing countries: "developed countries are more urbanized than developing ones - urban population represents about 75% of the total population for the former countries and 37% for the latter [...]; urban areas generates 85% of GNP in high-income countries compared to only 55% in developing countries [...]" (Bertinelli and Black, 2004: 80). The urban areas of developing countries have frequently processes of rapid economic transformation, reflected by a sharp decline in the proportion of employment in agriculture, and offsetting increases in the share of industry, trade and services (Jones, 2002). However, urbanization has not only positive effects. Urbanization creates unbalances between different regions of the country; urbanization can destroy important agricultural and environmental areas that were used to provide fresh food water and other environmental services of proximity former more contained cities and towns; finally urbanization is many times associated with urban poverty, linked to unemployment, lack of access to housing, education and health services (Simões Lopes and Pontes, 2010). Even in very well planned rich cities, there are empty new houses where there are no jobs and signs of slum resilience and developments in unplanned locations (Ooi and Phua, 2007). In developing countries, the mismatch between population growth - due to high fertility rates and high levels of internal migrations -, employment growth and the increase in housing, causes the existence of huge disqualified peripheries (the slums). In all cases, the urban areas faced the challenge of become more sustainable areas (or less unsustainable). Dentinho (2009) argues that urban unsustainability is caused by technological and institutional inadequacy. The technological inadequacy leads to increasing and irreversible degradation of natural capital; institutional inadequacy, in its turn, allows free access to urban space by creating mechanisms like "commons tragedy ". The main economic drivers of major towns in the developing world are actually royalties of oil and mineral exports and the public spending they allow (Dentinho, 2011); the issue is where the money goes and what are the effects of that allocation on urban and rural sustainability? To answer this question for Timor Leste we first develop a conceptual tool suitable to assess the impacts on population and employment distribution associated with the spatial distribution of private investment on the exploitation of natural resources and the public investment that uses the rents coming from the exploitation of natural resources (point 2). After (point 3) we describe the Timor Leste shortly, and in point 4 we operationalize and calibrate the conceptual model presented in the point 2 and show and discuss the results. Finally, in the last section, some conclusions and recommendations are highlighted.